How do Calendar Anomalies Affect an Investment Choice? A Proposal of an Analytic Hierarchy Process Model - Rossi, Matteo; Marcarelli, Gabriella; Ferraro, Antonella; Lucadamo, Antonio (International Journal of Economics and Financial Issues, 2020)
In recent years, financial markets changed for globalization. Today, a wide range of investment opportunities is available to investors. In this new scenario, markets are related, but each of them has specific characteristics with particular opportunities for investors. An investment choice can be influenced by numerous qualitative and quantitative factors that often conflict with one other. Thus, portfolio management choice is a multi-criteria decision problem today, so it requires flexible and analytic decision tools for investors. For this task, the Analytic Hierarchy Process (AHP) is suitable. We propose a theoretical model to analyse an investment choice problem taking into account different financial markets. Return of stock market, performance of the government bond and calendar effects in the financial markets considered are the evaluation criteria used in our model. The proposed model has strengths and weaknesses. First, through the AHP methodology the problem can be decomposed into a dominance hierarchy. Then, the subjective judgements expressed by means of pairwise comparisons are cheked in order to verify their consistency. Moreover, it is flexible and allows us to check if the ranking changes based on varying criteria weights. However, in that model we assume that criteria and alternatives are independent. Furthermore, our research lacks of a numerical application to test the model. Keywords: AHP, calendar anomalies, government bonds, stock market, investment choice. JEL Classifications: C13, C44, G11, G14, G40 DOI: https://doi.org/10.32479/ijefi.8995